HEPATITIS B TESTING IN THE FAMILIES AND VILLAGES OF FIVE YOUNG ESKIMOS WITH PRIMARY HEPATOCELLULAR CARCINOMA - BOSS, LESLIE P.; BENDER, THOMAS R.; SCHREEDER, MARSHALL T.; LANIER, ANNE P.; HARDISON, H. HUNTLEY; MAYNARD, JAMES E. (Oxford University Press, 1981)
A 15-year-old female Eskimo and a 22-year-old male Eskimo from a south western Alaskan village (population 540) were diagnosed as having primary hepatocellular carcinoma (PHC) in December, 1977. The fathers of both patients also died of PHC. Three additional cases of PHC affecting young Alaskan Eskimos had been diagnosed since 1972, all from neighboring viliages. Four of the five young patients were positive for hepatitis B surface antigen (HBsAg), and the family members of three patients were all positive for HBsAg or antibody to this antigen (anti-HBs). The other two families had no members positive for HBsAg. The prevalence of HBsAg in the villages of these patients ranged from 0–5%, and the prevalence of anti-HBs ranged from 3–25%. This part of Alaska has a high rate of infection with hepatitis B virus and an increased incidence of PHC. However, other Alaskan villages of similar ethnic background have considerably higher rates of hepatitis B infection than the four villages described and to date they have no PHC. This suggests that genetic and/or environmental factors in addition to hepatitis B infection may have a role in the etiology of PHC in Alaska.